European and Australian Cerebral Palsy Surveillance Networks Working Together for Collaborative Research - Sellier, Elodie; McIntyre, Sarah; Smithers-Sheedy, Hayley; Platt, Mary Jane; on behalf of SCPE and ACPR Groups (Neuropediatrics, 2020)
Aims This study aims to describe and compare goals and methods, characteristics of children with cerebral palsy (CP), and to compare prevalence of CP in the Surveillance of Cerebral Palsy in Europe (SCPE) and the Australian Cerebral Palsy Register (ACPR).Methods This study compares the objectives of the two networks and their working practices; key documents from both above-mentioned networks were used. Children included in the comparison of the descriptive profile and prevalence measures were born between 1993 and 2009 for Australian data and between 1980 and 2003 for SCPE.Results SCPE contributed 10,756 cases and ACPR 6,803. There were similar distributions of motor type, severity, and gestational age groups, except for the proportion of the lowest gestational age category (range, 20–27 weeks) which was twice higher in the ACPR (13 vs. 7%). Associated impairment proportions were also similar except for severe vision impairment which was more than twice as high in SCPE as in the ACPR (11 vs. 4%), but most likely due to a subtle difference in definitions. Prevalence rates were comparable at the same time point in the different groups of birth weight, and declined over time, except for the moderately low birth weight in ACPR.Conclusion Two CP networks representing two continents have compared their major characteristics to facilitate the comparison across their study populations. These characteristics proved to be similar with only marginal differences. This gives additional strength to the observation in both networks that CP prevalence is decreasing which is of great importance for families and health care systems.
Keywords: cerebral palsy; epidemiology; registers; prevalence